Sistem Informasi Penerimaan Siswa Baru SMP Negeri Kabupaten Nias Utara Berbasis Web - Purba, Desinta; Baeha, Josep Cristabel (UNIKA Santo Thomas, 2022)
Registration of new students is an annual cycle experienced by all educational institutions, both public and private institutions. The education office of North Nias Regency has noted that the number of junior high schools, especially public junior high schools in North Nias Regency is 49 units. Of all the schools, the admission of new students is still manual. Judging from the distance, time, and opportunities for parents who want to register their children to school are limited, which is caused by work and other activities, and especially at the time of registration of new students, schools are always filled with prospective students and parents of students who want to register. So that the assigned officer or teacher becomes overwhelmed and sometimes the file that has been received by the officer or teacher assigned is scattered or does not match the file. So that it makes teachers who want to compile files overwhelmed or confused in compiling them. North Nias district education office even from the school also needs a web-based information system that is able to process data for prospective new students. This system is also expected to be able to minimize data collection errors and also file preparation by officers or teachers who have been assigned